Puppet Show as Popular Culture in Bali: The Revitalization of Puppet Performing Arts through the Rhetoric Originality of Wayang Cenk Blonk - I Nyoman Suaka; I Made Budiasa (Universitas Udayana, 2024)
The contemporary history of Balinese performing arts is characterized by the inception of the renowned puppeteer Wayan Nardayana’s monumental puppet show, popularly known as puppet or wayang Cenk Blonk, derived from the name of their punakawan characters (servants to the main hero) who are comical, intelligent, critical, and possessed of a broad range of social knowledge. The emergence of the Cenk Blonk puppeteer since the early 1990s has led to a significant expansion of the wayang performance in Bali, from rural older adult to urban youth audiences. This article examines the popularity of puppeteer Nardayana, focusing on his ability to incorporate rhetoric into his performances. The data was taken from the dialogue texts of his performances and examined with rhetoric theory. The study demonstrates that puppeteer Nardayana’s popularity is attributed to his ability to present stories in a refreshing, original, critical, and entertaining style without sacrificing the traditional puppetry principles. This study contributes to appreciating the revitalization of traditional art in a globalized era.